Molecular Epidemiology of Azole-Resistant Aspergillus fumigatus in France Shows Patient and Healthcare Links to Environmentally Occurring Genotypes - Rocchi, Steffi; Sewell, Thomas R.; Valot, Benoit; Godeau, Chloé; Laboissiere, Audrey; Millon, Laurence; Fisher, Matthew C. (Frontiers in Cellular and Infection Microbiology, 2021)
Resistance of the human pathogenic fungus Aspergillus fumigatus to antifungal agents is on the rise. However, links between patient infections, their potential acquisition from local environmental sources and links to global diversity remain cryptic. Here, we used genotyping analyses using 9-microsatellites in A. fumigatus, in order to study patterns of diversity in France. In this study, we genotyped 225 local A. fumigatus isolates, 112 azole susceptible and 113 azole resistant, collected from Bourgogne-Franche-Comté region (Eastern France) and sampled from both clinical (n=34) and environmental (n=191) sources. Azole resistant clinical isolates (n=29) were recovered mainly from cystic fibrosis patients and environmental isolates (n=84) from market gardens and sawmills. In common with previous studies, the TR34/L98H allele predominated and comprised 80% of resistant isolates. The genotypes obtained for these local TR34/L98H isolates were integrated into a broader analysis including all genotypes for which data are available worldwide. We found that dominant local TR34/L98H genotypes were isolated in different sample types at different dates (different patients and types of environments) with hospital air and patient’s isolates linked. Therefore, we are not able to rule out the possibility of some nosocomial transmission. We also found genotypes in these same environments to be highly diverse, emphasising the highly mixed nature of A. fumigatus populations. Identical clonal genotypes were found to occur both in the French Eastern region and in the rest of the world (notably Australia), whilst others have not yet been observed and could be specific to our region. Our study demonstrates the need to integrate patient, healthcare and environmental sampling with global databases in order to contextualise the local-scale epidemiology of antifungal resistant aspergillosis.